2021
DOI: 10.14814/phy2.15113
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the growth hormone secretagogue receptor 1a (GHS‐R1a) in the brain

Abstract: The review presents data on the expression of growth hormone secretagogue receptor 1a (GHS‐R1a) in the brain regions in model animals (zebrafish, rodents, primates), and in the human brain. Studies show widespread distribution of the receptor in the brain, which evidences the involvement of the receptor in many physiological processes. Using various organisms, data have been obtained regarding the participation of the GHS‐R1a in the regulation of the anti‐ and pro‐inflammatory response, proliferation, and apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…As a ghrelin and LEAP2 receptor, GHSR is widely distributed in the hypothalamus ( 53 ). In addition to neuropeptides, we examined the expression of GHSR.…”
Section: Discussionmentioning
confidence: 99%
“…As a ghrelin and LEAP2 receptor, GHSR is widely distributed in the hypothalamus ( 53 ). In addition to neuropeptides, we examined the expression of GHSR.…”
Section: Discussionmentioning
confidence: 99%
“…Acyl-ghrelin, a major form of ghrelin, has been shown to exert neuroprotective effects against PD by binding to GHS-R1a, which is expressed in the striatum and SNpc. 73,74 It has been found to inhibit apoptosis by enhancing mitophagy and mitochondria biogenesis. 28 A study using caloric-restricted ghrelin KO or ghrelin WT mice has indicated AMPK as a target protein to maintain energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin is primarily secreted by oxyntic cells of the gastric mucosa, and its action is due to acylation process that allows its binding to growth hormone secretagogue receptor (GHSR), highly expressed in ARC ( 104 106 ). However, it is important to note that GHSR is differently expressed in ARC neuronal populations: about 90% of NPY/AgRP expressed GHSR compared to ~10% POMC neurons ( 107 , 108 ). Consequently, ghrelin mainly activates NPY/AgRP neurons promoting food intake ( 109 ).…”
Section: The Circadian System: An Orchestra Of Signals Synchronizes F...mentioning
confidence: 99%